Object Morphology—A Protean Generalization of Object-Oriented Paradigm - Šlajchrt, Zbyněk (2016)
Modeling protean objects, i.e. objects adapting their structure and behavior dynamically with respect to a changeable environment, is often challenging in traditional object-oriented languages. According to the author, the root cause of this problem lies in the class-based conceptual framework embedded in the foundation of the object-oriented para-digm. The proposed paradigm Object Morphology (OM) is greatly influenced by prototype theory developed in the field of cognitive psychology. OM abandons the notion of class and suggests, instead, that the abstractions of protean objects should be established through the construction of morph models describing the possible forms of those objects. This the-sis defines the theoretical foundations of OM, which is further used to specify the elements of prototypical object-oriented analysis. An important part of this work is also a proof-of-concept implementation of an OM framework in Scala.